Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x + (-25)=-12-(-4)
x -25 = -8
x =-8 +25
x =17
b) 2x + 5 = -3
2x =-3-5
2x =-8
x =-8:2=-4
d) 9(x + 7) -12 =24
9x + 63 =24 + 12
9x +63 =36
9x =36 -63
x =-27 : 9 =-3
nhớ tk cho mình nha
a) 1-5+7-8+4-1+5-7+8
=(1-1) - (-5+5) -(7-7) -(-8+8) +4
=0
b)=-39+9
=-30
c)=(20-20)-(-4+4)-(8-8)-17+15
=-2
d)= (13-13)-(-98+98)-(91-91)-75
=-75
a: \(\Leftrightarrow2x-2+4x+8=-12\)
=>6x+6=-12
=>6x=-18
hay x=-3
b: \(\Leftrightarrow-10x-15-12+9x=13\)
=>-x-27=13
=>-x=40
hay x=-40
c: \(\Leftrightarrow-10x+70+20-5x=-15\)
\(\Leftrightarrow-15x=-105\)
hay x=7
d: \(\Leftrightarrow8x-12-7x+14=10\)
=>x+2=10
hay x=8
e: \(\Leftrightarrow-12x-18+14x+2=2\)
=>2x-16=2
hay x=9
a)25/x+1 - 7/6 = 1/3 - 0,5
25/x+1 - 7/6 = 1/3 -1/2
25/x+1 - 7/6 = -1/6
25/x+1 = -1/6 + 7/6
25/x+1 = 1
25/x+1 = 25/25
=>25 = x + 1
x = 25 - 1
x = 24
.\(a.56-\left(3-12\right)=x+5\)
\(x+5=56-\left(3-12\right)\)
\(x+5=56-\left(-9\right)\)
\(x+5=47\)
\(x=47-5=42\)
\(\)
\(\)
\(x+4=-51\)\(x+4=-51\)\(-51=x+4\)\(-51=x+\text{4}\)
\(-\frac{1}{10}< =x< =\frac{3}{5}\)
\(\frac{-4}{9}< x< =\frac{2}{3}\)
#)Giải :
7/12 - ( 2x - 4/9 ) = 1
2x - 4/9 = 7/12 - 1
2x - 4/9 = -5/12
2x = -5/12 + 4/9
2x = 1/36
x = 1/36 : 2
x = 1/72
#~Will~be~Pens~#
7/12 - (2x - 4/9 ) = 1
2x - 4/9=7/12-1
2x -4/9=-5/12
2x=-5/12+4/9
2x=1/36
x=1/36 :2
x=1/72